2017
DOI: 10.3177/jnsv.63.237
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Cyanidin-3-Glucoside Attenuates Platelet Granule Release in Mice Fed High-Fat Diets

Abstract: Summary Platelet granule release is considered an important target for preventing and treating cardiovascular diseases (CVDs). Cyanidin-3-glucoside (Cy-3-g) is a predominant bioactive anthocyanin compound in many edible plants and has been reported to be protective against CVDs by attenuating platelet dysfunction. However, direct evidence of the action of Cy-3-g on platelet granule secretion in purified platelets from in vivo assays is still poor. In the present study, we demonstrated that dietary supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…12,13 We previously demonstrated that cyanidin-3-O-β-glucoside (Cy-3-g), the major bioactive compound in anthocyanins, inhibited platelet aggregation, activation, granule secretion, and thrombus formation in vitro, and in vivo in both animal and dyslipidemic human subjects. 10,11,14,15 Our in vitro studies also showed that Cy-3-g induced megakaryocyte apoptosis in the human megakaryoblastic Meg-01 cells 16 and promoted apo-ptosis of activated platelet. 17 However, the effective levels of Cy-3-g were determined at a range between 10 to 100 μmol/L.…”
Section: Introductionsupporting
confidence: 62%
“…12,13 We previously demonstrated that cyanidin-3-O-β-glucoside (Cy-3-g), the major bioactive compound in anthocyanins, inhibited platelet aggregation, activation, granule secretion, and thrombus formation in vitro, and in vivo in both animal and dyslipidemic human subjects. 10,11,14,15 Our in vitro studies also showed that Cy-3-g induced megakaryocyte apoptosis in the human megakaryoblastic Meg-01 cells 16 and promoted apo-ptosis of activated platelet. 17 However, the effective levels of Cy-3-g were determined at a range between 10 to 100 μmol/L.…”
Section: Introductionsupporting
confidence: 62%
“…It has also been demonstrated that C3G significantly ameliorated hyperglycemia and insulin sensitivity in vivo (Tsuda et al, 2003). A recent in vivo study reported that C3G inhibited release of purified platelet granule and protected against CVD and thrombosis (Zhou et al, 2017). Furthermore, it also diminishes blood glucose level and modulates insulin sensitivity in type 2 diabetic mice.…”
Section: Pharmacological Mechanisms Of Anthocyanins In Metabolic Syndmentioning
confidence: 99%
“…It has also been proven that C3G had synergistic effect with acarbose, a inhibitor of α-glucosidase used in the treatment of diabetes. Furthermore, C3G treatment resulted in increased insulin secretion compared with the control diabetic group, and is a potential phytotherapeutic agent for the prevention of diabetes (Zhou et al, 2017).…”
Section: Pharmacological Mechanisms Of Anthocyanins In Metabolic Syndmentioning
confidence: 99%
“…Pigmented rice-derived polyphenols have also shown inhibition of platelet ATP secretion. Zhou et al [63] conducted in vivo trials on mice fed with high-fat diets. The impact of dietary intervention with the anthocyanin cyanidin-3-glucoside (C3G) purified from black rice was investigated.…”
Section: Impact Of Polyphenols On Platelet Aggregationmentioning
confidence: 99%
“…Mice randomly allocated to one of the 3 groups with 20 subjects for each group: control group (normal diet), high-fat diet (HFD group), or an HFD supplemented with C3G Both Decreased platelet activation, serum lipid levels, and inhibits platelet ATP release [63] In vivo Red wine polyphenols (Provinols™) 149 (uniephrectomized male Sprague-Dawley rats)…”
Section: Bothmentioning
confidence: 99%